Overlying Fluoroscopy and Preacquired CT Angiography for Road-Mapping in Cerebral Angiography - Lin, C.-J.; Blanc, R.; Clarençon, F.; Piotin, M.; Spelle, L.; Guillermic, J.; Moret, J. (American Journal of Neuroradiology, 2010)
SUMMARY: We describe our preliminary experience using a road-mapping procedure that involves combining preacquired CTA with real-time fluoroscopy. This maneuver facilitates navigation in supra-aortic vessels from the arch to skull base levels. It requires less contrast than is used for traditional road-mapping while potentially reducing the hazard of thromboembolic events associated with direct catheterization. The accuracy of registration between the 2 volume datasets seems satisfactory for clinical practice. APanteroposteriorCTACT angiography3DRA3D rotation angiographyMIPmaximum intensity projection.